DETERMINAN PERILAKU PENGGUNAAN KONDOM DALAM UPAYA PENCEGAHAN HUMAN IMMUNODEFICIENCY VIRUS (HIV) PADA ANAK BUAH KAPAL (ABK) - Ratna Sari Fitria; Sori Muda Sarumpaet; Peny Ariani (Jurnal Kajian Kesehatan Masyarakat, 2019)
The ship′s crew are a group at risk of HIV / AIDS. Behavior prevention of HIV transmission can be done by using condoms when conducting risky sexual activities on a regular basis. Based on reports in 2018 HIV sufferers in the city of Lhokseumawe were 76 cases, in Indonesia there were 301,959 cases of HIV, and according to UNAIDS there were 39.6 million cases of HIV sufferers. The purpose of this study was to analyze the determinants of condom use behavior in an effort to prevent Human Immunodeficiency Virus (HIV) the ship′s in Krueng Geukuh port in North Aceh Regency in 2019. This study used a cross sectional approach with a total sample of 100 respondents of the ship′s at the port of Kreung Geukuh North Aceh Regency by purpose sampling Data analysis using univariate, bivariate and multivariate with chi-square test using softwear SPSS 25.0 for windows. The results showed that there was a significant correlation between psychosocial factors (p = 0.021), knowledge factors (p = 0.281), individual perceptions (p = 0.004), age factors (p = 0.916), educational factors (p = 0.200) with behavior condom use in an effort to prevent Human Immunodeficiency Virus (HIV), and there was no correlation with risk sex status factors (p = 0.301) and domicile factors (p = 0.222) with condom use behavior in an effort to prevent Human Immunodeficiency Virus (HIV) Suggestions that researchers recommend are to further improve the behavior of prevention of HIV / AIDS transmission with the use of condoms and to be able to work together across sectors that related to the prevention of Sexual Transmited Diseas (STDs) and HIV.